Synthetic control of magnetic resonance properties towards metal-based electron paramagnetic resonance imaging - Campanella, Anthony John, author; Zadrozny, Joseph, advisor; Shores, Matthew, committee member; Bandar, Jeff, committee member; Wu, Mingzhong, committee member (Colorado State University. Libraries, 2023)
Electron paramagnetic resonance imaging (EPRI) is the electron-spin analogue to conventional biological (nuclear) magnetic resonance imaging (MRI) whereby unpaired electron spins are probed in order to generate an image. The greater sensitivity of electron spins to their environment can thus be leveraged to capture detailed chemical information from the surroundings, producing an image of the local physiology that adds an extra dimension to the already powerful anatomical information gained from MRI. To move EPRI a step closer to common utilization, paramagnetic probes must be developed to sense the local environment using safe low-frequency microwaves at high (ca. 1.5 T) magnetic fields. Paramagnetic metal complexes are ideal candidates due to their electronic structures but have not been investigated for such purposes. The goal of this dissertation is to develop fundamental design principles to improve the utility of metal complexes as EPRI probes. Presented herein is the first comprehensive collection of experimental investigations to this end. Firstly, a method for improving signal sharpness is investigated, where exhaustive spectroscopic and computational studies suggest differences in relaxation dynamics as being a key factor in spectral linewidth (Chapters 2 and 3). A highly tunable clathrochelate structure is developed, inducing an unusual coordination geometry around the Ni(II) ion affording an 11 cm−1control of zero-field splitting (Chapter 4). The temperature dependence of zero-field splitting is examined in a series of Mn(II) complexes where an unusually high temperature sensitivity is found in the solid state (Chapter 5). Finally, the utility of metal complexes as environmental sensors is demonstrated with a pair of Mn(II) complexes showing that increasing magnetic anisotropy is a design strategy for enhancing microviscosity sensitivity (Chapter 6). The learned design principles will serve as a foundation for the design of metal-based EPRI agents towards improving the non-invasive diagnostic capabilities.
Keywords: electron paramagnetic resonance imaging; electron paramagnetic resonance; metal complex